Study on Plasma D-Dimer for Early Diagnosis of Ischemic Stroke - Sarkar, Paritosh Kumar; Baqui, Murshed; Chowdhury, Mohammad Shah Jahirul Hoque; Saha, Konol; Alamgir, Md Abdullah; Iqbal, Roushan; Ghose, Swapon Kumar; Habib, Mansur; Hoque, Md Azharul; Mondal, Badrul Alam; Quraishi, Firoz Ahmed; Mohammad, Quazi Deen (Journal of Dhaka Medical College, 2016)
Background: Plasma D-Dimer is a biomarker of thrombo-embolism and a sensitive indicator of subclinical coagulopathy. Its level begins to rise within the first 6 hours of onset of symptoms of acute ischemic stroke. The availability of a rapid diagnostic test like plasma D-Dimer in acute ischemic stroke would be a substantial adjunct to CT and MRI. The test for plasma D-Dimer is quick and easy to perform based on principle of latex agglutination. This study is taken to estimate Plasma D-Dimer level in ischemic stroke patients and to see its role in early diagnosis, and also to differentiate different types of acute ischemic stroke in Bangladeshi population. Methods: This case control study was conducted in Dhaka Medical College Hospital (DMCH) from July 2010 to June 2012. Plasma D-Dimer was estimated by latex agglutination method in DMCH laboratory. Fifty stroke patients (age, 58.36±14.8 years; sex-M/F: 34/16) and 50 age matched control (58.80±15.01 years; sex-M/F: 36/14) were enrolled. In ischemic stroke group all patients were presented from 4 hours to 3 days. CT scan of brain revealed both cortical and subcortical lesion (56%), subcortical lesion (34%) and cortical lesion (10%). The CT volume of the involved brain lesion was 19.95±4.92 cm3. The value of plasma D-Dimer were evaluated in both control and ischemic stroke patients, correlated with CT size of infract and different types of acute ischemic strokes. Results: Qualitative analysis of plasma D-Dimer reveals 76% positive and 24% negative in the ischemic stroke group. On the other hand, plasma D-Dimer value was only 6% positive and 94% negative in the control group. Qualitative analysis of plasma D-Dimer differs significantly (c2=50.64; p=0.001) between the two groups. The analysis also reveals 76% sensitivity and 94% specificity of the Plasma D-Dimer test. Quantitative measurement of plasma D-Dimer (p=0.001) was 804±120 hg/ml and 126±16 hg/ml in ischemic and control groups respectively. The plasma concentration of D-Dimer between the two groups was statistically highly significant (t=31.21; p=0.001). Mean plasma D-Dimer level was highest in embolic infarct (1700±964 hg/ml) followed by atherothrombotic (536±234 hg/ml) and lowest in lacunar (100±00 hg/ml) subtype. J Dhaka Medical College, Vol. 24, No.2, October, 2015, Page 117-125